How do firms cope with losses from extreme weather events? - EIB Working Paper 2022/10 - European Investment Bank (European Investment Bank, 2022)
When firms suffer losses from extreme weather events, such as storms, foods, droughts or landslides, it has implications for their investment plans and the finance their need. This paper investigates the investment and financing decisions of firms that experience monetary losses due to such extreme weather events. It looks at firms in 41 economies, mainly emerging and developing markets, using data from the EBRD-EIB-World Bank Enterprise Survey. It finds that firms hit by extreme weather are more likely to invest in long-term assets, in a way that fits with the need to either replenish damaged capital or to adapt to climate change. In addition, they are more likely to integrate climate-friendly measures in their production processes. Although these firms have higher needs for bank credit, they are not more likely to be credit constrained than the average firm. Nonetheless, they face higher loan rejection rates and have, on average, more debt than otherwise comparable firms. This suggests that climate change has the potential to erode the quality of firm balance sheets over time.